Dire la ville en grec aux époques antique et byzantine Actes du colloque de Créteil, 10-11 juin 2016 - Lopez-Rabatel, Liliane; Mathé, Virginie; Moretti, Jean-Charles (Littérature & Linguistique, 2020)
Based upon all sorts of available texts, the proceedings of this colloquium are an invitation to question the words and the discourses concerning the city in the territories in which the Greek language was spoken during Antiquity and the Middle Ages. The study of vocabulary and language seeks to better understand the meaning of the words themselves, their evolution over time, and their variations according to region, as well as the diversity of their usage in various types of texts. This study aims at clarifying the mental images both underlying the usage of these words and resulting from it. How are the words of the city formed? How do words shape the city? The articles focus on one term in isolation, on a semantic field, or on a work related to urban worlds, real or fictitious. They treat the city as a whole: its edifices, its activities considered as strictly urban, or its inhabitants. The articles are organized into four categories entitled "People and cities", "Components and composition of urban spaces", "Naming and classifying cities", and "Cities in an empire".